Sex Differences in Odor Hedonic Perception: An Overview - Bontempi, Charlotte; Jacquot, Laurence; Brand, Gérard (Frontiers in Neuroscience, 2021)
Odor hedonic evaluation (pleasant/unpleasant) is considered as the first and one of the most prominent dimension in odor perception. While sex differences in human olfaction have been extensively explored, gender effect in hedonic perception appears to be less considered. However, a number of studies have included comparisons between men and women, using different types of measurements (psychophysical, psychophysiological,...). This overview presents experimental works with non-specific and specific odors are separately presented as well as experimental studies comparing healthy participants vs patients with psychiatric disorders. Contrary to sensitivity, identification or discrimination, the overall literature tends to prove that no so clear differences occur in odor hedonic judgement between men and women. On the whole, gender effect appears more marked for specific than non-specific odors and is almost never reported in psychiatric diseases. These findings are discussed in relation to the processes classically implied in pleasantness rating and emotional processes.